Pesan Moral Dalam Visual Peringatan Darurat: Analisis Semiotika Charles Sanders Peirce - Rahmat Hidayat; Moehammad Gafar Yoedtadi (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2026)
Visual elements such as symbols or images are often used to evoke public emotions and convey moral messages through viral posts on social media. The viral post about the